The ZDHHC13/ZDHHC17 subfamily: From biological functions to therapeutic targets of diseases - Ying Zhang; Sisi Fan; Lu He; Lanfang Li (Elsevier, 2024)
The ZDHHC13/ZDHHC17 subfamily belongs to the zinc finger DHHC-domain containing (ZDHHC) family, including ZDHHC13 and ZDHHC17. Recent studies have shown that the ZDHHC13/ZDHHC17 subfamily is involved in various pathological and physiological processes, including S-palmitoylation, Mg2+ transport, and CALCOCO1-mediated Golgiphagy. Moreover, the ZDHHC13/ZDHHC17 subfamily plays a crucial role in the occurrence and development of many diseases, including Huntington disease (HD), osteoporosis, atopic dermatitis, diabetes, and cancer. In the present review, we describe the distribution, structure, and post-translational modifications (PTMs) of the ZDHHC13/ZDHHC17 subfamily. Moreover, we effectively summarize the biological functions and associated diseases of this subfamily. Given the pleiotropy of the ZDHHC13/ZDHHC17 subfamily, it is imperative to conduct further research on its members to comprehend the pertinent pathophysiological mechanisms and to devise tactics for managing and controlling various diseases.